First report of the enset root mealybug Paraputo ensete (Williams & Matile-Ferrero) (Hem.: Pseudococcidae) on banana in Ethiopia - Fikadu Erenso; Guy Blomme; Georg Goergen; Mitiku Muanenda; Elizabeth Kearsley; Temesgen Addis (International Journal of Tropical Insect Science, 2023)
Enset root mealybugs, a major pest affecting the cultivation of the enset crop in the Ethiopian highlands, have for the first time been observed on banana mats indicating the potential host status of Musa spp. These observations were made under natural conditions in backyard gardens in the Gedeo zone, southern Ethiopia, on the root system of banana mats of the ‘Pisang Awak’ (local name ‘Feranji Muz’, ABB genome group) landrace. Here, we confirm the identification of the collected enset root mealybug specimens on banana mat root systems as Paraputo ensete (Williams & Matile-Ferrero) (Hemiptera: Pseudococcidae) through DNA analysis.

Enset (Ensete ventricosum) clone selection by farmers and their cultural practices in southern Ethiopia - Zerihun Yemataw; Hussein Mohamed; Mulugeta Diro; Temesgen Addis; Guy Blomme (Genetic Resources and Crop Evolution, 2014)

Report on the 32th Annual Meeting of the Working Group “Beneficial Arthropods and Entomopathogenic Nematodes” - Annette Herz; Ralf-Udo Ehlers; Johannes A Jehle; Eva Fritsch; Karin Undorf-Spahn; Stefanie Schulze-Bopp; Diana Schneider; Johannes A Jehle; Yvonne Rondot; Annette Reineke; Dietrich Stephan; Temesgen Addis; et al. (Journal of Plant Diseases and Protection, 2014)